Influence of the curing method on the post-polymerization shrinkage stress of a composite resin - Leonardo Gonçalves Cunha; Roberta Caroline Bruschi Alonso; Eduardo José Carvalho de Souza-Junior; Ana Christina Elias Claro Neves; Lourenço Correr-Sobrinho; Mário Alexandre Coelho Sinhoreti (University of São Paulo, 2008)
The aim of this study was to evaluate the effect of different curing methods on the stress generated by the polymerization shrinkage of a restorative composite in two moments: immediately after light exposure and after 5 min. Photoactivation was performed using two different light sources: (1) xenon plasma arc (PAC) light (1,500 mW/cm2 - 3s) and (2) a quartz-tungsten-halogen (QTH) light with three light-curing regimens: continuous exposure (40 s at 800 mW/cm2 - CL); soft-start (10 s at 150 mW/cm2 and 30 s at 800 mW/cm2 - SS) and intermittent light [cycles of 4 s (2 s with light on at 600 mW/cm2 and 2 s of light off), for 80s - IL]. The composite resin was applied between two 5-mm diameter metallic rods, mounted in a servohydraulic machine. The maximum stress was recorded immediately after light exposure (FF) and after 5 min (5F). The results were submitted to ANOVA and Tukey's test (5%). For each method, the results obtained in FF and 5F were, respectively: CL (3.58 and 4.46 MPa); SS (2.99 and 4.36 MPa); IL (3.11 and 4.32 MPa) and PAC (0.72 and 3.27 MPa). The stress generated by the polymerization shrinkage during light exposure can be associated with the photoactivation method used. A significant increase in the stress level was observed during the post-curing period up to 5 min, for all evaluated methods.